2019
DOI: 10.1088/1755-1315/358/3/032006
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and cell imaging of nitrogen-doped graphene quantum dot conjugated indomethacin

Abstract: The nitrogen-doped graphene quantum dot conjugated indomethacin (N-GQD-IDM) was synthesized by an amide reaction. The results of FTIR indicated that the synthesis of N-GQD-IDM was successful. It was then co-cultured with MCF-7 cells, and obvious fluorescence was observed under a laser confocal scanning microscope. With the increase of incubation time, the material accumulated significantly in the cells and the fluorescence intensity of the cells was slightly improved. This compound could be suggested as a prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The results of the fluorescence images showed high recognition of GQDs-PEG. Nonetheless, Feng et al synthesized nitrogen-doped GQDs reacted with indomethacin [ 254 ]. This fluorescent probe was then incubated with breast cancer cells (MCF-7) for imaging through a Laser Scanning Confocal Microscope.…”
Section: Reviewmentioning
confidence: 99%
“…The results of the fluorescence images showed high recognition of GQDs-PEG. Nonetheless, Feng et al synthesized nitrogen-doped GQDs reacted with indomethacin [ 254 ]. This fluorescent probe was then incubated with breast cancer cells (MCF-7) for imaging through a Laser Scanning Confocal Microscope.…”
Section: Reviewmentioning
confidence: 99%
“…Moreover, starting materials, synthesis methods, and experimental parameters have a direct effect on the physicochemical attributes of GQDs. Recently, it has been reported that heteroatom-doped GQDs afforded high quantum yield (QY), surface/volume ratio, and resistance to photobleaching. Furthermore, the suitability of heteroatom-doped GQDs (sulfur-doped, boron-doped, chlorine-doped, and nitrogen-doped) for use in cellular applications can be assessed according to their QY and water dispersity. Investigations have identified that the catalytic activity of GQDs is due to selective deactivation of surface carboxylic, carbonyl, or hydroxyl groups. Sun and co-investigators found that the carbonyl group can act as a catalytic site, while OC-O- and hydroxyl groups act as a substrate-binding spot and an inhibitor, respectively.…”
Section: Graphene Quantum Dotsmentioning
confidence: 99%
“…The use of such a novel methodology will benefit cancer theranostics . Feng et al investigated conjugates of indomethacin (IDM) and nitrogen-doped GQDs for cancer cell recognition and cellular imaging . Here, EDC-NHS chemistry was used for the conjugation of IDM with N-GQDs.…”
Section: Graphene Quantum Dots-based Theranostic Strategiesmentioning
confidence: 99%
See 2 more Smart Citations